Запорозька Січ у житті та творчості М. П. Киценка. (Zaporizhzhia Historical Review, 2021)
The role of Zaporizka Sich in the life of M.P. Kytsenko is being defined. It is demonstrated that he bend every effort to creating a preserve on Khortytsa island, though his plans were realized but partially.